Creator and Creation / Siti Hamidah Abdul Hamid and Mohd Shah Tumin - Abdul Hamid, Siti Hamidah; Tumin, Mohd Shah (Faculty of Art and Design, 2021)
Today’s extreme of wealth and economic growth, in particular, construction industry, is intolerable. The thought remains focused on both countries and its societies’ intelligence with regards to savage construction growth. In thinking about, and acting upon the unique building creation by mankind, we need wisdom to match Allah SWT as the Creator. The creation remains in close relationship to the Creator. Despite the Creator is always in advance of creation and so it is able to will the existence of human creation through knowledge transfer. Human intellect is supported by the power of remembrance and thoughts to Allah SWT. The artwork is the combination of medium and high rise buildings which are created by human beings, while the word ‘Allah’ as the Creator of the universe is a well blended part of the building. It is the symbol of the Creator, presently and constantly involved in the world in various ways which is represented by the use of mixed colors. The attitudes toward the earth and its resources are implied by the belief in Allah as the Creator in the Islamic religious tradition is vital. Human beings continue to make unique building designs by using advanced technology today. However, one undeniable fact is that no matter how far man has explored and achieved, the man himself remains a mystery and seeks actual human reality. All the answers reflect to Allah the Creator as the reflection of the buildings in the artwork.